2020
DOI: 10.1111/pce.13926
|View full text |Cite
|
Sign up to set email alerts
|

Molecular hydrogen–induced salinity tolerance requires melatonin signalling inArabidopsis thaliana

Abstract: Melatonin (MT) plays positive roles in salinity stress tolerance. However, the upstream signalling components that regulate MT are poorly understood. Here, we report that endogenous MT acts downstream of molecular hydrogen (H2) in the salinity response in Arabidopsis. The addition of hydrogen‐rich water and expression of the hydrogenase1 gene (CrHYD1) from Chlamydomonas reinhardtii increased endogenous H2 and MT levels and enhanced salinity tolerance. These results were not observed in the absence of serotonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 70 publications
1
24
0
Order By: Relevance
“…In the previous reports, the expression of hydrogenase1 gene from Chlamydomonas reinhardtii ( CrHYD1 ) in Arabidopsis represents an interesting method to assess the functions of endogenous production of H 2 in plant cells, since molecular hydrogen derived from CrHYD1 expression could modify the stomatal closure [ 20 ] and improve salinity tolerance [ 19 ]. Here, compared to those in the wild-type (WT) with or without being transformed with the empty vector (EV), six CrHYD1 lines not only showed increased H 2 production in the presence of CAR ( Figure S6 ), but importantly, displayed the lower residues of CAR in leaves, especially CrHYD1-3 , CrHYD1-5 , and CrHYD1-6 ( Figure 6 A), and similar beneficial roles of endogenous H 2 were discovered according to the changes in stomatal bioassays [ 20 ] and salinity phenotypic analysis [ 19 ]. Under the identical treatments, contrasting changes in endogenous GSH were also observed ( Figure 6 B), thus reflecting the possible negative correlation between CAR residues and GSH contents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous reports, the expression of hydrogenase1 gene from Chlamydomonas reinhardtii ( CrHYD1 ) in Arabidopsis represents an interesting method to assess the functions of endogenous production of H 2 in plant cells, since molecular hydrogen derived from CrHYD1 expression could modify the stomatal closure [ 20 ] and improve salinity tolerance [ 19 ]. Here, compared to those in the wild-type (WT) with or without being transformed with the empty vector (EV), six CrHYD1 lines not only showed increased H 2 production in the presence of CAR ( Figure S6 ), but importantly, displayed the lower residues of CAR in leaves, especially CrHYD1-3 , CrHYD1-5 , and CrHYD1-6 ( Figure 6 A), and similar beneficial roles of endogenous H 2 were discovered according to the changes in stomatal bioassays [ 20 ] and salinity phenotypic analysis [ 19 ]. Under the identical treatments, contrasting changes in endogenous GSH were also observed ( Figure 6 B), thus reflecting the possible negative correlation between CAR residues and GSH contents.…”
Section: Resultsmentioning
confidence: 99%
“…However, CHT was hardly absorbed by plants compared with CAR [ 18 ]. Genetic evidence showed that the expression of the hydrogenase1 gene ( CrHYD1 ) from Chlamydomonas reinhardtii not only increased endogenous H 2 production, but also confers Arabidopsis tolerance against salinity [ 19 ] and drought stress [ 20 ]. Additionally, H 2 could influence nitric oxide [ 21 ], abscisic acid [ 22 ], auxin [ 23 ], melatonin [ 19 ], and glutathione [ 24 ] signaling in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Salt stress has become a severe global problem, limiting agricultural production and leading to substantial economic losses worldwide ( Su et al, 2021 ). Salt has two detrimental effects on plants: osmotic stress and ion poisoning ( Van Zelm et al, 2020 ).…”
Section: Roles Of Melatonin In Plant Abiotic Stress Responsesmentioning
confidence: 99%
“…Interestingly, the production of H 2 has been observed in plants under the normal or stressed conditions [ 10 , 11 , 12 ], although its detailed synthetic pathway (s) are not fully elucidated. Further studies have revealed that H 2 played an important role in defense responses of plants to abiotic stresses [ 13 , 14 , 15 ], plant growth [ 16 ], and secondary metabolism [ 17 ]. H 2 was beneficial to postharvest preservation of fruits (kiwifruit [ 18 , 19 ] and tomato [ 20 ]) and cut flowers (rose [ 21 ], lily [ 22 ], and Lisianthus [ 23 ]).…”
Section: Introductionmentioning
confidence: 99%